An activity based costing model for outbound logistics costs measurement and management: a case study - Afonso, Paulo (2015)
There is a lack of models, applications and empirical results that demonstrate the applicability of activity based costing (ABC) systems in the context of logistics processes as well as its analysis and discussion. The ABC model for outbound logistics presented in this article allows the computation of different cost objects (e.g. cost per route, cost per product segment) as well as helps with relevant information for operational and strategic management. The case study was developed in a Portuguese benchmark company whose core business is focused on the storage and distribution of wood and wood-based products. The application of the model showed that there is a trade-off between transportation costs and gross margins which should be managed according with both operational and strategic constraints and objectives. It was concluded that the pricing policy should take into account the product category, the distance, the value and the quantity to be transported.